Seismic Stability Analysis of Soil Nail Walls Using the Upper Bound Method - Imani, Meysam; Babaei Pouya, Omid (Transportation infrastructure geotechnology, 2021)
Soil nailing can be considered one of the most useful methods for ensuring the stability of excavations. The static stability analysis of the soil nail walls is necessary for practical applications. Moreover, for the walls that are intended to be used in a long time, seismic stability analysis is also required, which is the main subject of the present paper. The upper bound method of limit analysis was used to develop the formulation of the safety factor of the soil nail walls. The effect of both the horizontal and vertical accelerations of the earthquake was considered in the calculations. It was assumed that the wall is not inclined with respect to the vertical direction. Also, the method presented in this paper is capable of considering the effects of both the surcharge loads and different inclinations of the ground above the wall. The obtained results show that the horizontal and vertical accelerations of the earthquake result in decreasing the safety factor of soil nail walls. Also, the safety factor of the stability of the soil nail walls is affected by different parameters, including the soil and nail properties and the geometrical configuration of the problem. Extensive sensitivity analyses were performed to investigate the effect of all important parameters on the safety factor.